Genetic diversity and phylogeography of Chimaera monstrosa (Linnaeus, 1758) in the Mediterranean Sea: insights from COI mitochondrial DNA analysis - Basusta, Nuri; Saglam, Naim (Nature Portfolio, 2026)
Chimaera monstrosa (Linnaeus, 1758) is a deep-water cartilaginous fish classified as Vulnerable globally and Near Threatened in the Mediterranean by the IUCN, yet its population genetic structure remains poorly characterised across much of its range. Here, we report the first mitochondrial cytochrome c oxidase subunit I (COI) sequences of C. monstrosa from Turkish Mediterranean waters, obtained from five specimens collected as bycatch during commercial bottom trawling at 460-550 m depth in & Idot;skenderun Bay. These sequences were analysed together with 60 publicly available COI sequences from the Mediterranean Sea and the Atlantic Ocean using maximum likelihood phylogenetic analysis and TCS haplotype network reconstruction. All Turkish specimens clustered within the Mediterranean clade and were distributed across three haplotypes (H1, H2, and H3), showing close affinity with samples from other Mediterranean localities. Across the full dataset of 65 sequences (596 bp), 30 haplotypes were identified, with high haplotype diversity (Hd = 0.909) and low nucleotide diversity (pi = 0.00544). AMOVA revealed strong and significant inter-basin structure (Phi ST = 0.682, P < 0.001), with Mediterranean and Atlantic haplotypes forming non-overlapping regional clusters. Neutrality tests produced significantly negative Fu's Fs (- 22.528, P < 0.001), yet the multimodal mismatch distribution does not support simple demographic expansion; these results are best treated as model-dependent summaries given the geographically structured nature of the dataset. The findings support genetic differentiation between Mediterranean and Atlantic populations of C. monstrosa and suggest that these populations merit independent consideration in future conservation assessments.
Keywords: Chimaera Monstrosa; Cytochrome C Oxidase Subunit I (Coi); Haplotype Network; Mediterranean-Atlantic Differentiation; Molecular Phylogeography; Population Structure